HMGB1-TLR4 Signaling Contributes to the Secretion of Interleukin 6 and Interleukin 8 by Nasal Epithelial Cells. Issue 3 (May 2016) - Shimizu, Shino; Kouzaki, Hideaki; Kato, Tomohisa; Tojima, Ichiro; Shimizu, Takeshi
Background: Alarmins play important roles in the pathogenesis of inflammatory and autoimmune diseases. However, the role of the alarmin protein high-mobility group box 1 (HMGB1) in upper airway inflammation is unclear. Objective: To determine if HMGB1 is present in the nasal mucosa and, if so, to elucidate its role in upper airway inflammation. Methods: Nasal secretions were collected from a total of 32 patients with chronic rhinosinusitis with nasal polyp, allergic rhinitis, and control subjects. The concentration of HMGB1 in nasal secretions and its tissue and cellular localization were examined by enzyme immunoassays and immunofluorescent staining of nasal polyps and cultured nasal epithelial cells. We then examined whether nasal epithelial cells secrete HMGB1 after inflammatory stimulation by tumor necrosis factor (TNF) α. The effects of HMGB1 on the production and secretion of interleukin (IL) 6 and IL-8 were also examined in cultured nasal epithelial cells. Results: Significantly higher concentrations of HMGB1 were found in nasal secretions from patients with chronic rhinosinusitis with nasal polyp or allergic rhinitis compared with the control subjects. HMGB1 expression was localized in the nuclei of epithelial cells and other constitutive cells in nasal polyps and in the nuclei of cultured nasal epithelial cells. TNF-α stimulated the production and secretion of HMGB1 by cultured nasal epithelial cells. HMGB1 stimulated the production and secretion of IL-6 and IL-8 by cultured nasal epithelial cells, and anti–toll-like receptor 4 blocking antibody significantly inhibited HMGB1-induced secretion of IL-6 and IL-8. Conclusions: Nasal secretions contain substantial amounts of HMGB1. TNF-α stimulates the production of HMGB1, which, in turn, upregulates the production and secretion of IL-6 and IL-8 by nasal epithelial cells via toll-like receptor 4, which indicated that HMGB1 plays an important role in the pathogenesis of upper airway inflammation.